Neural Network to Solve Concave Games. (10th March 2014) - Liu, Zixin; Wang, Nengfa
Abstract : The issue on neural network method to solve concave games is concerned. Combined with variational inequality, Ky Fan inequality, and projection equation, concave games are transformed into a neural network model. On the basis of the Lyapunov stable theory, some stability results are also given. Finally, two classic games' simulation results are given to illustrate the theoretical results.